2018
DOI: 10.1007/s40272-018-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alginate in Gastroesophageal Reflux in Infants

Abstract: BackgroundGuidelines are contradictory regarding the use of alginate in infants with persisting gastroesophageal reflux (GER). While The British National Institute for Health and Care (NICE) guidelines consider alginate as a treatment option, the guidelines of the European and North-American Societies for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN, NASPGHAN) do not recommend alginates.AimsWe assessed the efficacy of alginate to reduce GER episodes in infants.MethodsIn a prospective, observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Very recently, Salvatore et al demonstrated that alginate-based formulations reduced both acid and nonacid reflux episodes assessed by esophageal pH impedance and symptoms reported during the investigation in 31/40 (77%) infants with persisting GER symptoms non-responsive to behavior and diet modification [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Very recently, Salvatore et al demonstrated that alginate-based formulations reduced both acid and nonacid reflux episodes assessed by esophageal pH impedance and symptoms reported during the investigation in 31/40 (77%) infants with persisting GER symptoms non-responsive to behavior and diet modification [19].…”
Section: Discussionmentioning
confidence: 98%
“…[17]. We considered persistent regurgitation when I-GERQ-R was above the cut-off limit or normal (≥16), as already reported [18,19].…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Medication and investigations are not required in the management of uncomplicated regurgitation. If the infant is in a very distressed state, mainly after a feeding or between the feeds, treatment with alginate may be given a chance [23]. A survey in Italy revealed that 56% of general pediatricians prescribe proton pump inhibitors for infants with gastroesophageal reflux (GER) symptoms associated with unexplained crying and/or irritability, and 38% of the pediatricians prescribe PPI in infants with uncomplicated recurrent regurgitation and vomiting [24].…”
Section: Methodsmentioning
confidence: 99%
“…Surface barrier agents work by acting as a physical barrier to prevent damage to the esophageal mucosa by refluxed gastric acid 8. Sodium alginate, a polysaccharide derived from brown seaweed, has been used in the treatment of gastroesophageal reflux disease 90,109. In the presence of gastric acid in the stomach, alginate precipitates and forms a viscous gel, thereby increasing the viscosity of feeds and reducing gastroesophageal reflux 42,45,90,110,111.…”
Section: Managementmentioning
confidence: 99%